Chlamydia cases in women of reproductive age, 2006–2020: an analysis of surveillance data from Southern China - Peizhen Zhao; Peng Liang; Jinshen Wang; Wenqian Xu; Shujie Huang; Cheng Wang (BMC Public Health)
Abstract Background Chlamydia is common among women of reproductive age and can cause serious health issues. This study aimed to examine the trends and factors linked to newly diagnosed and reported chlamydia cases in women aged 15–49 in Guangdong Province from 2006 to 2020. Methods We included all newly diagnosed and reported chlamydia cases from January 1, 2006, to December 31, 2020. Data from 21 cities in Guangdong Province were sourced from the National Notifiable Infectious Disease Reporting Information System in China. Temporal trends were analyzed using Joinpoint regression models. City-level factors (population density, net migration rate, and male-to-female sex ratio) were derived from the Guangdong Statistical Yearbook and the Guangdong Health and Family Planning Statistical Yearbook. Quasi-Poisson regression models were used to explore the relationship between sociodemographic factors and chlamydia incidence. Results From 2006 to 2020, 523,367 new chlamydia cases were reported among women of reproductive age in Guangdong. The mean reported rate was 122.6 per 100,000 population over 15 years, significantly increasing from 1.4 in 2006 to 179.7 in 2020 (average annual percent change [AAPC] = 47.4%, 95% CI: 42.8%-52.2%, P < 0.05). The highest rate was 196.8 per 100,000 population in 2019. Among older women, 9,045 cases were reported, with a mean reported rate of 4.9 per 100,000, rising significantly from 0.01 in 2006 to 9.6 in 2020 (AAPC = 52.6%, 95% CI: 30.3%-78.8%, P < 0.05). The reported rate among women of reproductive age correlated with the net migration rate (RR = 1.2; 95% CI: 1.2–1.3) and the ratio of those participating in child-bearing insurance to the permanent population (RR = 1.5; 95% CI: 1.4–1.6). Conclusion The reported rate of new chlamydia cases among women of reproductive age was significantly higher than among older adults and increased markedly from 2006 to 2020. These findings underscore the urgent need for targeted prevention strategies for women of reproductive age.